Handheld volumetric manual compression‐based quantitative microelastography. Issue 6 (27th February 2020) - Fang, Qi; Frewer, Luke; Zilkens, Renate; Krajancich, Brooke; Curatolo, Andrea; Chin, Lixin; Foo, Ken Y.; Lakhiani, Devina D.; Sanderson, Rowan W.; Wijesinghe, Philip; Anstie, James D.; Dessauvagie, Benjamin F.; et al.
Abstract: Compression optical coherence elastography (OCE) typically requires a mechanical actuator to impart a controlled uniform strain to the sample. However, for handheld scanning, this adds complexity to the design of the probe and the actuator stroke limits the amount of strain that can be applied. In this work, we present a new volumetric imaging approach that utilizes bidirectional manual compression via the natural motion of the user's hand to induce strain to the sample, realizing compact, actuator‐free, handheld compression OCE. In this way, we are able to demonstrate rapid acquisition of three‐dimensional quantitative microelastography (QME) datasets of a tissue volume (6 × 6 × 1 mm 3 ) in 3.4 seconds. We characterize the elasticity sensitivity of this freehand manual compression approach using a homogeneous silicone phantom and demonstrate comparable performance to a benchtop mounted, actuator‐based approach. In addition, we demonstrate handheld volumetric manual compression‐based QME on a tissue‐mimicking phantom with an embedded stiff inclusion and on freshly excised human breast specimens from both mastectomy and wide local excision (WLE) surgeries. Tissue results are coregistered with postoperative histology, verifying the capability of our approach to measure the elasticity of tissue and to distinguish stiff tumor from surrounding soft benign tissue. Abstract : Novel handheld compression optical coherent elastography technique using natural motion of user's hand to induce strain to the sample is demonstrated in this article. This technique allows rapid acquisition of three‐dimensional microelastograms of 6 × 6 × 1 mm 3 volume in 3.4 seconds, without the use of external actuator. Results of freshly excised human breast tissues demonstrate its capability of distinguishing stiff tumor from soft benign tissues.